Influence of Workload and Normative Commitment on Employee Performance - Riana Kartika; Ni Kadek Widiastuti (International Journal of Economics Development Research (IJEDR), 2023)
Human Resources are an essential component of every organization. To be successful, an office must have knowledgeable, highly skilled, and committed employees who carry out their duties in the best possible way. Human resources are a source of organizational strength derived from individuals who can be utilized. The efficacy of an organization's employees has a significant impact on its success. This objective is shared by the Population and Civil Registration Office of Buleleng Regency. This research seeks to answer the question, to what extent do burden and normative commitment affect employee performance at the Population and Civil Registration Office of Buleleng Regency. This study's population consisted of 72 and 33 civil servants, including all employees. This research used 51 respondents through Probability Sampling Technique. The data demonstrates that workload significantly and positively affects productivity. This suggests that employees perform better when their workload is lower, but their performance declines when their workload increases. Similarly, normative commitment exhibits a notable and constructive impact on the performance of employees. This means that if normative commitment is increased, employee performance will follow suit, and conversely, if normative commitment is decreased, employee performance will also decrease.